Ex Vivo Assessment of Carbon Tetrachloride (CCl4)-Induced Chronic Injury Using Polarized Light Spectroscopy. Issue 12 (December 2013) - Ahmad, Manzoor; Ali, Safdar; Mehmood, Malik Sajjad; Ali, Hamid; Khurshid, Ahmat; Firdous, Shamaraz; Muhammad, Saleh; Ikram, Masroor
The liver performs various functions, such as the production and detoxification of chemicals; therefore, it is susceptible to hepatotoxins such as carbon tetrachloride (CCl4 ), which causes chronic injury. Thus, assessment of injury and its status of severity are of prime importance. Current work reports an ex vivo study for probing the severance of hepatic injury induced by CCl4 with polarized light over the spectral range 400–800 nm. Different concentrations of CCl4 were used to induce varying severity of hepatic injury in a rat model. Linear retardance, depolarization rates, and diagonal Mueller matrix elements (m22, m33, and m44 ), were successfully used as the distinguishing criterion for normal and different liver injuries. Our results show that linear retardance for injured liver samples with lower doses of CCl4 tends to increase when compared with normal liver samples, while samples injured at higher doses of CCl4 offer almost no retardance. Total, linear, and circular depolarizations follow decreasing trends with increased liver injury severity over the entire investigated wavelength range. Linear polarization states were observed to be better maintained as compared to circular polarization states for all samples. Furthermore, numerical values of diagonal elements of the experimentally measured Mueller matrix also increase with increasing doses of CCl4 . Liver fibroses, change in transport albedo, and the relative refractive index of the extracellular matrix caused by CCl4 are responsible for the observed differences. These results will provide a pathway to gauge the severity of injury caused by toxic chemicals.